2020
DOI: 10.1542/peds.2020-019844
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Polymorphisms and Multisystem Inflammatory Syndrome in Children

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…It is thought that the host factors are the significant contributors to MIS rather than viral factors, according to a study done in London involving children infected with SARS-CoV-2 [ 7 ]. This can be translated into the adult population since they can present similarly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that the host factors are the significant contributors to MIS rather than viral factors, according to a study done in London involving children infected with SARS-CoV-2 [ 7 ]. This can be translated into the adult population since they can present similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Critical COVID-19 is a feature of acute respiratory distress syndrome (ARDS) with or without the multi-inflammatory syndrome [ 10 ]. In contrast, MIS-A manifests with no or minimal pulmonary features, hypoxemia, or radiological evidence of pulmonary involvement [ 7 ]. In addition, MIS-A tends to have a temporal space from the initial COVID-19 infection, usually appearing at least two weeks after the initial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Because MIS-C is a late presentation, the virus is often not present or found at very low levels in respiratory secretions. Therefore, whole-genome analysis has been difficult in this condition, and only a few reported sequences are available [ 149 , 150 ]. Although the pathogenesis of MIS-C is not well understood, it has been suggested that components of the virus may act as superantigens to provoke a polyclonal T-cell expansion [ 151 , 152 ] making it conceivable that viral variants may be more or less likely to cause disease.…”
Section: Biological Differences Between Genomic Variantsmentioning
confidence: 99%
“…Although the pathogenesis of MIS-C is not well understood, it has been suggested that components of the virus may act as superantigens to provoke a polyclonal T-cell expansion [ 151 , 152 ] making it conceivable that viral variants may be more or less likely to cause disease. The available sequences suggest that MIS-C associated viruses might be drawn from several distinct lineages that are representative of circulating virus without any genetic similarities that tie them together [ 150 ]. However, it is notable that the original experience with the virus in China did not detect any MIS-C, raising the possibility that this is presentation is linked to later forms of the virus.…”
Section: Biological Differences Between Genomic Variantsmentioning
confidence: 99%
“…Bununla birlikte, bazı çocukların PCR testi pozitiftir. Mevcut vaka serilerinde, hem PCR hem de seroloji uygulanan 783 çocuk hastanın %60'ında PCR negatif ve seroloji pozitif, %34'ünde her iki testte de pozitif ve %5'inde ise her iki testte de negatif saptanmıştır(2,6,8,10,13).MIS-C'nin Çin ve COVID-19'dan etkilenen diğer Asya ülkelerinde tanımlanmaması gerçeği, koronavirüslerdeki varyasyonlara veya bu popülasyonların artan duyarlılık veya genomik varyasyonuna ilişkin spekülasyonlara yol açmıştır(14).MIS-C'li 11 çocukta SARS-CoV-2 viral sekanslarını inceleyen bir çalışmada, MIS-C'siz akut COVID-19'lu çocuklardan alınan viral sekanslarla karşılaştırıldığında herhangi bir farklılık tespit edilmemiştir(15). Bu ön veriler, neden bazı çocukların SARS-CoV2 enfeksiyonu sonrası multi sistemik enflamasyon geliştirdiğini, diğerlerinin ise geliştirmediğini sadece viral faktörlerin açıklamadığını göstermektedir.…”
unclassified